Effectiveness of Flipped Classroom Model on EFL Students' English Proficiency: A Meta-Analysis Study - Muabidah, Umi; Rozal, Edi; Andriani, Reni (FKIP Universitas Lampung, 2025)
Effectiveness of Flipped Classroom Model on Students' English Language Ability: A Meta-Analysis Study. Various studies have attempted to examine the impact of using flipped classrooms on students' English language skills at various levels of education in Indonesia. However, the conclusions of these studies are heterogeneous. Objective: This study aims to analyze the effectiveness of flipped classrooms in English learning compared to traditional models. Method: The research method used is meta-analysis. A total of 20 primary studies published between 2019-2024 were included in this meta-analysis. Findings: The result of the combined effect size analysis using the random-effect estimation model is g = 0.80 (p < 0.05). This value indicates that flipped classrooms have a large and significant impact on students' English skills compared to traditional models. In addition, the analysis of moderator variables shows that the effectiveness of flipped classrooms on students' English skills differs based on educational level (Qb = 16.46; p < 0.05), experimental class capacity (Qb = 26.14; p < 0.05), and type of ability measured (Qb = 76.11; p < 0.05). Conclusion: The findings confirm that flipped classrooms have a significant impact on students' English language skills compared to traditional models. This effectiveness depends on the context, such as educational level, class capacity, and types of skills being measured. Therefore, these results highlight the need to adjust the instructional design of flipped classrooms based on student characteristics, class size, and learning focus. These findings provide direction for educators to be more careful in designing flipped classroom-based learning and encourage researchers to develop further studies that consider contextual variables to produce more effective implementations in various educational settings. Keywords: english, flipped classroom model, meta-analysis, effect size.